PECULIARITIES OF PHYSICAL-CHEMICAL CHARACTERISTICS OF FLUXING AGENTS, USED IN TECHNOLOGIES OF ELECTROSLAG REMELTING - S. N. Zherebtsov; M. V. Romanovskij (Литьë и металлургия)
The experimental and literature data on characteristics and functions of fluxing agents and slags, applied for running of stable melting processes in different electroslag technologies, are generalized. The energy connections of cations and anions in slag systems are examined. The formulas of calculation of the slag melts basic capacity depending on chemical composition of fluxing agents are offered. The densities are investigated and melting temperatures of different fluxing agents are given.